2022
DOI: 10.1002/jbm4.10638
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Loss of Maxillary Molars in Young Mice Leads to Bilateral Condylar Adaptation and Degenerative Disease

Abstract: The adaptive response of the mandible and temporomandibular joint (TMJ) to altered occlusion in juvenile patients is presently unclear. To address this question, we established a mouse model in which all molars were extracted from the maxillary right quadrant in prepubertal, 3-week-old mice and analyzed morphological, tissue, cellular, and molecular changes in the mandible and condyle 3 weeks later. Unilateral loss of maxillary molars led to significant, robust, bilateral changes, primarily in condylar morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…According to Rosado et al ( 2021 ), there is a notable decrease in bone volume in the glenoid fossa among those who are edentulous. Furthermore, a further investigation conducted by Chen et al ( 2022 ) revealed that the loss of teeth, even unilaterally, can lead to a reduction in condyle bone volume in an in vivo experimental model. Hence, the duration of edentulism may influence the morphological alterations of the condylar process and, consequently, its positioning within the TMJ.…”
Section: Discussionmentioning
confidence: 98%
“…According to Rosado et al ( 2021 ), there is a notable decrease in bone volume in the glenoid fossa among those who are edentulous. Furthermore, a further investigation conducted by Chen et al ( 2022 ) revealed that the loss of teeth, even unilaterally, can lead to a reduction in condyle bone volume in an in vivo experimental model. Hence, the duration of edentulism may influence the morphological alterations of the condylar process and, consequently, its positioning within the TMJ.…”
Section: Discussionmentioning
confidence: 98%
“…The TMJ is classified as a compound joint. The TMJ consists of hard tissue, soft tissue, ligaments, muscles of mastication and neck, nerves, and blood vessels [1,10,11]. There are two main movements at the TMJ joint (Figure 2 and 3), namely rotation and glide or translational movement.…”
Section: Temporo-mandibular Joint (Tmj)mentioning
confidence: 99%
“…Glide or translational movement (Figure 4) is a movement in which each object point moves concurrently with the same speed and direction. Translation happens when the (lower) jaw moves forward, protruding more so that the ramus, condyles, and teeth all move in the same degree and direction of inclination in the masticatory system [1,9,10,12].…”
Section: Temporo-mandibular Joint (Tmj)mentioning
confidence: 99%